Distribution and fungicide sensitivity of Colletotrichum species complexes from rubber tree in Hainan, China - Cao, X.; Xu, X.; Che, H.; West, J.S.; Luo, D.
Colletotrichum gloeosporioides and C. acutatum species complexes are causal agents of Colletotrichum leaf disease (CLD)of rubber trees worldwide. To determine the geographic distribution of Colletotrichum species complexes associated with CLD of rubber trees in Hainan, China, and their sensitivity to fungicides used in the region, a total of 275 Colletotrichum isolates were collected from 52 rubber tree plantations in 11 counties. These isolates were identified based jointly on morphological characteristics and PCR-based methodology. Of these isolates, 78 and 22 percent belonged to the C. gloeosporioides species complex (CGSC)and the C. acutatum complex (CASC), respectively. The incidence of CGSC isolates was greater than the CASC in all counties sampled. The incidence of CASC isolates appeared to be lower in the western and central south of Hainan than in other regions. There was no association in their presence at a given plantation between the two species complexes. The in vitro sensitivity of these two species complexes to carbendazim, chlorothalonil, and four demethylation inhibitor (DMI)fungicides (difenoconazole, propiconazole, myclobutanil, and prochloraz)was determined. Carbendazim was effective against CGSC but not against CASC with mean ED50 values of 0.176 and 2.182 ?g/ml, respectively. CASC isolates were more sensitive to difenoconazole, propiconazole, and myclobutanil (mean ED50 values of 0.177, 0.129, and 1.424 ?g/ml, respectively)than CGSC isolates (mean ED50 values of 0.710, 0.348, and 3.496 ?g/ml, respectively). Mean ED50values of CGSC against chlorothalonil and prochloraz were 173.341 and 0.035 ?g/ml, respectively; corresponding values for CASC were 151.441 and 0.040 ?g/ml. These results suggest that prochloraz, propiconazole, and difenoconazole are effective against both species complexes.
Keywords: COLLETOTRICHUM